Determinants Of Individuals' Intentions To Use Central Bank Digital Currency (CBDC) In Kuching - Nur Amira Aina, Zulkarnain; Nur Zaimah, Ubaidillah (2023)
The aim of this research is to examines the relationship between perceived value and individuals' intention to use Central Bank Digital Currency (CBDC). Quantitative research methods were employed, and the data of 215 respondents was collected through online questionnaires. Statistical software (SPSS) was utilized for data analysis, including descriptive statistics, reliability analysis, Spearman's correlation coefficient, frequency distribution, and multiple regression analysis. The findings reveal correlations between perceived value, perceived innovativeness, perceived convenience, perceived trust, perceived risk, and intention to adopt CBDC. The results indicate positive correlations between perceived value and perceived convenience, perceived trust, as well as intention to adopt CBDC. Similarly, perceived convenience is positively correlated with perceived trust and intention to adopt CBDC. These correlations suggest moderate to strong positive relationships. The study highlights the importance of perceived value in influencing individuals' intentions to use CBDC. The results provide valuable insights for policymakers and stakeholders involved in the development and implementation of CBDC systems, emphasizing the need to consider factors such as convenience and trust to promote widespread adoption.